Assessing the impact of partial early retirement on self-perceived health, depression level and quality of life in Belgium: a longitudinal perspective using the Survey of Health, Ageing and Retirement in Europe (SHARE). Issue 3 (5th March 2020) - Wels, Jacques
Abstract: For about 20 years, Belgium has successfully implemented working-time reduction policies for the older workforce. However, the impact of such policies on health has not been explored yet. Using longitudinal data from Waves 5 and 6 of the Survey of Health, Ageing and Retirement in Europe (SHARE) (N = 1, 498), the paper assesses whether working-time reduction in late career is associated with a change in self-perceived health, depression (EURO-D) and quality of life (CASP-12). For that purpose, ordered logit and ordinary least squares regressions are performed, using four different models for defining working-time reductions. Results show that people reducing working time with or without additional social benefits tend to have a poorer self-perceived health at follow-up compared with people keeping the same or increasing working time. By comparison, people moving to retirement are more likely to present a better self-perceived health, depression level and quality of life compared to people increasing or keeping the same working-time level. Although, introducing an interaction effect, the paper shows that the change in quality of life for respondents reducing working hours in addition to social benefits tends to be less negative for those who wished to retire early at baseline than for those who did not.